#TITLE_ALTERNATIVE# - FADLI ADI ABIYASA (NIM 17503012), MOCHAMMAD
Leather is one of the oldest materials used by men as their daily equipment. Originally, leather is used to cover a human's body from cold and heat because human has very short body hair. As time goes by, people began to use leather for making other daily equipments such as clothing, shoes, bags, etc. Leather is famous for their strength, durability, warmth, and comfort. These characters are the reason why people from the ancient time to today's people choose leather as the basic material for making many interesting and important things for their lives. Having the economic and historical values in it, leather as a material and/or as a product is now a very expensive and luxurious industrial commodity. Leather uses and technologies are always developing thus making this material an important part of human's history and culture. Nowadays, leather industries are spreading all around the world helping many countries to develop their economical state. From small leather industries in Cibaduyut; Indonesia to big industries from around the world such as Nike, Adidas, Louis Vuitton, etc are using leather for their product's basic material. Beside the benefits mentioned earlier, leather also has several side effects that needs to be conserned. In the making process these industries also produce wastes. The wastes are various and require different treatment methods as well. Some of the wastes are no longer usable thus require complete destruction, while other wastes can still be used as materials for other products. These wastes are the pieces of leather that remained from the cutting process. This article reports on the study to find possibilities and chances of reusing the waste from cutting process into unique material for industrial purposes. The methods used for this purpose was by doing several experimental work to analyze leather reaction upon several treatments such as physic, chemical, etc.